Politik Islam Pengaruh terhadap Partisipasi Perempuan dalam Kepemimpinan Mahasiswa - Syaela, Balqis Najmi Aqila Putri; Fauziah, Firda Nur; Safitri, Risa Nur; Amanda, Shafira Putri; Sasabila, Zahrah; Suresman, Edi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study analyzes the influence of Islamic politics on women’s participation in student leadership. This issue is crucial because, although Islam provides space for women to engage in leadership, social and cultural barriers still limit their involvement.This research employs a descriptive qualitative method, utilizing semi-structured interviews with students and literature analysis from various scholarly sources. The findings indicate that an inclusive interpretation of Islamic politics can encourage women’s participation in student organizations, whereas more conservative understandings tend to be obstacles. Other factors, such as gender stereotypes, social norms, and cultural expectations, also play a role in shaping the dynamics of women’s leadership in academic environments. These findings highlight the need for a fair and contextual approach to understanding women’s roles in leadership. Affirmative policies, academic support, and leadership training programs can help increase women’s involvement in student organizations, fostering a more inclusive and equitable environment.